2001
DOI: 10.1080/003655201300191969
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori-induced Expression of Interleukin-8 and Cyclooxygenase-2 in AGS Gastric Epithelial Cells: Mediation by Nuclear Factor-κB

Abstract: NF-kappaB may play a novel role in expression of IL-8 and COX-2 in H. pylori-induced gastric inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 53 publications
1
42
0
Order By: Relevance
“…The adhesion of H. pylori to gastric epithelial cells was reported to activate nuclear factor kappa B (NFκB) and stimulate IL-8 production. 37) Yamaoka et al reported a remarkable increase of IL-6 and IL-8 levels in GC tissues, and concluded that IL-8 levels in GC tissues are largely independent of H. pylori infection. 38) In conclusion, the IL-8 level measured in drainage veins may reflect IL-8 production mainly by the primary lesion, and is valuable as an prognostic indicator or a risk factor for recurrence in GC patients, whereas the peripheral level of IL-8 is not.…”
Section: Discussionmentioning
confidence: 99%
“…The adhesion of H. pylori to gastric epithelial cells was reported to activate nuclear factor kappa B (NFκB) and stimulate IL-8 production. 37) Yamaoka et al reported a remarkable increase of IL-6 and IL-8 levels in GC tissues, and concluded that IL-8 levels in GC tissues are largely independent of H. pylori infection. 38) In conclusion, the IL-8 level measured in drainage veins may reflect IL-8 production mainly by the primary lesion, and is valuable as an prognostic indicator or a risk factor for recurrence in GC patients, whereas the peripheral level of IL-8 is not.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of NF-B with bacterial products (such as P. aeruginosa LPS) may trigger a proinflammatory and hyperproliferative cellular phenotype that, when deranged, can lead to neoplasia (such as cholesteatoma) or even contribute downstream gene products to the chronic inflammatory milieus that leads to malignancy (47). H. pylori infection induces cell proliferation (48) and overexpression of IL-8 and cyclooxygenase-2 in gastric epithelial cells (49), both events that may play a causative role in gastric carcinoma. Similarly, NF-B-mediated proinflammatory dysregulation has been associated with both the development of pancreatic cancer (50) and the progression to metastases (51).…”
Section: Discussionmentioning
confidence: 99%
“…pylori Infection of AGS Cells-The AGS human gastric epithelial cell line (gastric adenocarcinoma, ATCC CRL 1739) was obtained from the American Type Culture Collection (Manassas, VA). The cells were grown in RPMI 1640 medium (Invitrogen) supplemented with 10% fetal bovine serum (Invitrogen) in the presence of 100 units/ml penicillin-streptomycin at 37°C in a humidified chamber in 5% CO 2 (18). The cells were seeded at 1 ϫ 10 6 cells/dish in 10-cm cell culture dishes, grown to 80% confluency, and then washed twice with PBS, pH 7.4, and the medium was replaced with antibiotic-free RPMI 1640 medium.…”
Section: Methodsmentioning
confidence: 99%